2020
DOI: 10.1002/marc.201900668
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Indole Significantly Improves the Transfection Efficiency of Guanidinium‐Containing Poly(Methacrylamide)s

Abstract: A highly efficient transfection agent is reported that is based on terpolymer consisting of N‐(2‐hydroxypropyl)methacrylamide (HPMA), N‐(3‐guanidinopropyl) methacrylamide (GPMA), and N‐(2‐indolethyl)methacrylamide monomers (IEMA) by analogy to the amphipathic cell‐penetrating peptides containing tryptophan and arginine residues. The incorporation of the indole‐bearing monomer leads to successful plasmid DNA condensation even at a nitrogen‐to‐phosphate (N/P) ratio of 1. The hydrodynamic diameter of polyplexes i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…47,48 Since this feature is of great importance in applications such as drug or gene delivery, the guanidinium group is frequently exploited for the development of synthetic vectors. 46,[49][50][51][52][53] Regarding examples possessing vinylic polymeric backbones, Funhoff et al reported promising transfection and uptake in COS-7 cells for poly(3-guanidinopropyl methacrylate) (PGPMA) homopolymers prepared via free radical polymerization. 38 However, well-defined homopolymers of guanidinium-functional PAms have not been systematically studied as gene delivery vectors, nor compared with other cationic moieties.…”
Section: Introductionmentioning
confidence: 99%
“…47,48 Since this feature is of great importance in applications such as drug or gene delivery, the guanidinium group is frequently exploited for the development of synthetic vectors. 46,[49][50][51][52][53] Regarding examples possessing vinylic polymeric backbones, Funhoff et al reported promising transfection and uptake in COS-7 cells for poly(3-guanidinopropyl methacrylate) (PGPMA) homopolymers prepared via free radical polymerization. 38 However, well-defined homopolymers of guanidinium-functional PAms have not been systematically studied as gene delivery vectors, nor compared with other cationic moieties.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] GPMA was utilized due to the excellent ability of the guanidinium group to interact with genetic material, while HPMA was selected as a spacer unit to ensure the colloidal stability of the polyplexes. [ 26,36–39 ] IEMA was included to allow hydrophobic interactions with pDNA and cell membranes, to improve the cellular uptake and the transfection efficiency of the polyplexes. [ 26,36 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 26,36–39 ] IEMA was included to allow hydrophobic interactions with pDNA and cell membranes, to improve the cellular uptake and the transfection efficiency of the polyplexes. [ 26,36 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Moreover, we revealed that the incorporation of indole comonomer mimicking the side chain of the amino acid tryptophan, leads to a 200-fold increase of the transgene expression in comparison to a copolymer with comparable guanidinium content. [18] To understand to what extent the origin of the hydrophobic residue influences the internalization, complexation of pDNA, and the ability of the polymers to act as gene carriers, we designed terpolymers that contain side chains mimicking hydrophobic residues found in the side chains of amino acids.…”
mentioning
confidence: 99%